2021
DOI: 10.19088/k4d.2021.033
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Justice and Reconciliation in the Western Balkans: Approaches, Impacts and Challenges

Abstract: Countries in the Western Balkans have engaged in various transitional justice and reconciliation initiatives to address the legacy of the wars of the 1990s and the deep political and societal divisions that persist. There is growing consensus among scholars and practitioners that in order to foster meaningful change, transitional justice must extend beyond trials (the dominant international mechanism in the region) and be more firmly anchored in affected communities with alternative sites, safe spaces, and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…First, this research provides further evidence that interventions aimed at accentuating similarities and commonalities in contexts of conflict might be effective for paving the path towards reconciliation through creating more inclusive social identities. Second, this research points to the potential impact of story‐telling approach, as a commonly used approach used in various transitional justice and reconciliation initiatives (Haider, 2021). Indeed, studies have found that story‐telling can be very effective for reconciliation as it can facilitate empathy, perspective‐taking, as well as increased perceptions of commonalities and sharedness (Čehajić‐Clancy & Bilewicz, 2020; Oberpfalzerová et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…First, this research provides further evidence that interventions aimed at accentuating similarities and commonalities in contexts of conflict might be effective for paving the path towards reconciliation through creating more inclusive social identities. Second, this research points to the potential impact of story‐telling approach, as a commonly used approach used in various transitional justice and reconciliation initiatives (Haider, 2021). Indeed, studies have found that story‐telling can be very effective for reconciliation as it can facilitate empathy, perspective‐taking, as well as increased perceptions of commonalities and sharedness (Čehajić‐Clancy & Bilewicz, 2020; Oberpfalzerová et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…H. Haider (2018) notes that the countries of the Western Balkans have been involved in various justice processes for a long period of transition. There is a growing consensus among experts and specialists that to promote meaningful changes in the transitional justice system, it is necessary to go beyond the judicial processes prevailing in the region and to actively introduce alternative mechanisms and safe spaces of interaction in these affected communities.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the Western Balkans, which has a turbulent history, has been the focal point of numerous international efforts aimed at promoting peace, stability and cooperation among countries (Gajic and Ejdus 2018). Many cooperation mechanisms led by the international community have been established, some of which have survived (Haider 2019), and thus shaped the security landscape of the Western Balkans. This security cooperation found its foundations in the Stability Pact for Southeast Europe, which was established in 1999 (Gajic and Ejdus 2018).…”
Section: Overview Of Western Balkans Security Cooperationmentioning
confidence: 99%